Duration of Long Vowel Assimilation in Reciting Al-Qur'an Surah Al-Isra 'By International Qari' Year 2011 - Sri Octaviyanti; Siti Muharami Malayu; Rahlina Muskar Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the duration of assimilation on long vowels. The discussion studied in this study is the calculation of the duration of long vowel assimilation. This study uses acoustic phonetic theory by applying qualitative descriptive methods through observation and data editing techniques. To analyze the data, there are four analytical techniques that are applied, namely the note-taking technique, the sorting technique, the digitization, and the sound segmentation. Meanwhile, for measuring the duration of the assimilation of sounds, this study used the praat program version 4.0.27. After the data analyzed, the results of the study showed that the duration of the reading of long vowel assimilation by reciter 'DH sorted from the longest to the shortest, namely: the word [ʕaʈa: Ɂu] has a duration of 5,665 ms, the word [famaћawna: Ɂayata] has a duration of 4,922 ms, the word [dua : Ɂ] has a duration of 4,717 ms, the word [ʈa: Ɂira] has a duration of 4,106 ms, the word [u: la: Ɂika] has a duration of 4,021 ms, the word [waɁiða: Ɂaradna:] has a duration of 3,570 ms, the word [Ɂaradna: Ɂan] has a duration of 3,256 ms, the word [naʃa: Ɂ] has a duration of 2,844 ms, and the word [ha: Ɂu la: Ɂi] has a duration of 2,444 ms.